Fresh Water Algae from Running Streams of Gajurmukhi VDC, Ilam, Nepal - Rai, Shiva Kumar; Subba, Bharat Raj; Limbu, Kul Prasad (Our Nature, 2009)
In the present communication, a total 18 fresh water algae have been identified from streams and rivers of Gajurmukhi VDC, Ilam. The present study may help in the algal database of Nepal and to conserve aquatic biodiversity. Keywords: Algae, Chlorophyceae, Diatoms, Gajurmukhi, Ilam, Nepal doi: 10.3126/on.v6i1.1659 Our Nature (2008)6:80-81